Optimizing microsurgery training for plastic surgery resident: A systematic review - Gede Wara Samsarga; Agus Roy Rusly Hariantana Hamid; I Gusti Putu Hendra Sanjaya; I Gusti Ayu Putri Purwanthi; Ni Made Ratih Purnama Dewi (Indoscholar, 2022)
Background: Microsurgery for plastic surgery residents is complex and requires a long learning curve, psychomotor capabilities, and repeated practices. Microsurgery training for plastic surgical residents must be optimized due to the heavy workload during residency and the limited time available to master microsurgery skills. Methods: Electronic literature searching of the MEDLINE (PubMed), Cochrane, and Google Scholar databases was conducted. Studies that were eligible and published between January 2015 and September 2019 were chosen. Results: Surgical simulation platforms have been implemented as a result of new training methods to learn microsurgery. Plastic surgery residents can practice microsurgery in virtual, animal models, non-living models, and indirect patient practice. Resident’s competency scores and surgical performance improve as a result of simulation-based training. The demand for simulation-based training in plastic surgery residency programs is expected to rise as a result of its usefulness. A microsurgical skill evaluation is also a mandatory aspect of enhancing microsurgical skills for plastic surgery residents. Conclusion: Because there is limited time for formal microsurgery training in the operating room, plastic surgery residents must optimize their microsurgery skills outside of the operating room. Implementation of living and non-living models for microsurgery training and standardized objective assessment tools will further advance microsurgical skills in plastic surgery resident.